Comparison of the Dermatology Life Quality Index and the Children's Dermatology Life Quality Index in assessment of quality of life in patients with psoriasis aged 16–17 years. (12th November 2015) - van Geel, M.J.; Maatkamp, M.; Oostveen, A.M.; de Jong, E.M.G.J.; Finlay, A.Y.; van de Kerkhof, P.C.M.; Seyger, M.M.B.
Summary: Background: Dermatology Life Quality Index (DLQI) and Children's Dermatology Life Quality Index (CDLQI) are widely used to assess quality of life (QoL) in adults (≥ 16 years) and children (4–16 years) with psoriasis. In the age group 16–17 years, it is not known whether DLQI and CDLQI reflect QoL impairment in the same way. Objectives: To compare DLQI and CDLQI scores in patients with psoriasis aged 16–17 years. Methods: Patients with psoriasis aged 16–17 years were asked to complete both the DLQI and CDLQI. Results: Fifty‐six patients were included. There was a high correlation between DLQI and CDLQI scores ( r = 0·90, P < 0·001). The mean DLQI score (5·41 ± 5·20) was lower than the mean CDLQI (6·61 ± 5·74) ( P < 0·001). The major part of this difference (∆0·61) was caused by the low score regarding sexual difficulties in the DLQI (0·11 ± 0·49) and the high score concerning sleep in the CDLQI (0·71 ± 0·93). In addition, the question related to sports scored 0·34 in the DLQI but 0·86 in the CDLQI (∆0·52). The question related to work/study in the DLQI scored lower than the question on school/holiday in the CDLQI (∆0·41). Conclusions: In patients with psoriasis aged 16–17 years, DLQI and CDLQI scores closely correlate, but the mean DLQI score was lower than the mean CDLQI score. This was caused primarily by differences in the answers to questions regarding sexual difficulties and sleep. As the QoL impacts experienced by people aged 16–17 may differ from those experienced by children or adults, QoL measures designed for use in this age range may have advantages over both child‐ and adult‐specific measures. Abstract : What's already known about this topic? Psoriasis can have a negative impact on quality of life (QoL). Dermatology Life Quality Index (DLQI) and Children's Dermatology Life Quality Index (CDLQI) are commonly used dermatology‐specific QoL questionnaires used in adults (≥ 16 years) and children (4–16 years), respectively. What does this study add? In patients with psoriasis aged 16–17 years, DLQI and CDLQI scores closely correlated. Overall, DLQI scored lower than CDLQI. QoL measures designed for people aged 16–17 years may have advantages over both child‐ and adult‐specific measures. Linked Comment: Beattie, Br J Dermatol 2016 ; 174:21 . Plain language summary available online